PERSEPSI GURU TERHADAP PEMBELAJARAN MENGGUNAKAN KELAS DIGITAL - ABD GHOFUR; Evi Aulia Rachma (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2021)
This study aims to identify elementary school teachers' perceptions of learning using the digital classroom google classroom. This research involved 50 elementary grade IV teachers in Lamongan District. Analysis of the data used in this study is a descriptive quantitative analysis. Based on the results of the study it can be concluded that as many as 90% of teachers stated that they needed to attend training on learning using digital classes. As many as 74% of teachers said that they needed to implement learning by using digital classroom google classroom. Google classroom is flexible, so students can study at any time outside of school hours. Based on this, 86% of teachers stated that they needed to provide learning materials for students that could be accessed or used at any time outside of school hours through Google classroom. As many as 76% of teachers stated that google classroom made teachers more innovative in presenting learning materials. Then as many as 78% of teachers stated that the use of google classroom facilitated teachers in the process of assessing student assignments.